Characterization of IN738LC using in situ nanoindentation and crystal plasticity modeling - Amirhosein Mozafari; Bolin Fu; Darshan Chalapathi; Hamidreza Abdolvand (Materials & Design)
This study investigates the mechanical properties of IN738LC, a precipitation-hardened Ni-based superalloy recognized for its high strength and oxidation resistance at elevated temperatures. In situ nanoindentation tests are conducted in a scanning electron microscope (SEM) to study orientation dependent mechanical response of the alloy. Electron backscatter diffraction (EBSD) is conducted on grains and around precipitates before and after tests, while high resolution imaging is conducted for slip trace analysis. The analysis is performed on both as-received and heat-treated specimens to characterize their anisotropic mechanical responses. With the use of machine learning, the critical resolved shear stresses and hardening parameters are extracted to incorporate into a crystal plasticity finite element (CPFE) model so that the calculated macroscopic response of the alloy can be compared with the measured one. In situ nanoindentation tests reveal orientation-dependent load–depth responses and misorientation patterns, which are validated against simulations that accurately capture slip traces and pile-up morphologies. EBSD measurements taken before and after nanoindentation further show the crucial role of pre-existing orientation gradients in the calculated response of the material. Additionally, TiC precipitates are identified as potential fracture initiation sites under higher stress levels.